PENGARUH LINGKUNGAN SOSIAL TERHADAP PARTISIPASI OLAHRAGA REMAJA: KAJIAN LITERATUR SOSIOLOGI OLAHRAGA - Purnomo, Wahyu; Sinuhaji, Prestanto; Febri Kurniaman Zega, Josua; Indra Siregar, Yan; Arima, Putra; Pranda Ginting Suka, Zauzy; maktum Ritonga, Syairul; Pratama, Agung; Siahaan, Samuel (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Youth participation in sports is an important aspect in supporting the physical, mental, and social development of young generations. From the perspective of sports sociology, sports participation is influenced not only by individual factors but also by social environments such as family, school, peers, and society. This study aims to examine the influence of the social environment on youth sports participation through a literature review method. The research method used in this study is a literature review by analyzing various national and international journals, books, and scientific articles relevant to the research topic. The results of the study indicate that the social environment has a significant influence on adolescents’ interest, motivation, and involvement in sports activities. Family support, active school environments, and positive peer influence can increase youth participation in sports. On the other hand, limited sports facilities, low social support, and excessive use of technology can reduce adolescents’ sports activities. Therefore, collaboration among families, schools, communities, and governments is needed to create a supportive social environment for youth sports participation in order to develop healthy, active, and socially responsible young generations.